CHARCOAL IDENTIFICATION OF SAMPLES FROM CAPE KRUSENSTERN BEACH RIDGE SITE COMPLEX, NORTHWEST ALASKA - Puseman, Kathryn (PaleoResearch Institute) (the Digital Archaeological Record)
A total of four charcoal samples from the Cape Krusenstern beach ridge archaeological site complex in northwest Alaska were submitted for identification. This site complex is situated in the Cape Krusenstern National Monument.